Autoimmune Attack of the Neuromuscular Junction in Myasthenia Gravis: Nicotinic Acetylcholine Receptors and Other Targets - Paz, Mariela Laura (2019)
The nicotinic acetylcholine receptor (nAChR) family, the archetype member of the pentameric ligand-gated ion channels, is ubiquitously distributed in the central and peripheral nervous systems and its members are the targets for both genetic and acquired forms of neurological disorders. In the central nervous system nAChRs contribute to the pathological mechanisms of neurodegenerative disorders, such as Alzheimer and Parkinson diseases. In the peripheral nerve-muscle synapse, the vertebrate neuromuscular junction, ?classical? myasthenia gravis (MG) and other forms of neuromuscular transmission disorders are antibody-mediated autoimmune diseases. In MG, antibodies to the nAChR bind to the postsynaptic receptors and activate the classical complement pathway culminating in the formation of the membrane attack complex, with the subsequent destruction of the postsynaptic apparatus. Divalent nAChR-antibodies also cause internalization and loss of the nAChRs. Loss of receptors by either mechanism results in the muscle weakness and fatigability that typify the clinical manifestations of the disease. Other targets for antibodies, in a minority of patients, include muscle specific kinase (MuSK) and low-density lipoprotein related protein 4 (LRP4). This brief review analyzes the current status of muscle-type nAChR in relation to the pathogenesis of autoimmune diseases affecting the peripheral cholinergic synapse.